A Rare Case Study on Escherichia Coli Pneumonia - Sewada, Deepak; Saini, Shri Ram; kumar, Sunil (International Research Journal of Ayurveda & Yoga, 2021)
Pneumonia (from the Greek pneuma, "breath") is an infection and inflammation of the lower respiratory tract (bronchioles and alveoli) that can be fatal. It is caused by inhaled bacteria and viruses. High temperature, shortness of breath, fast breathing, severe chest pain, and a productive cough with thick phlegm are all common symptoms. Community-acquired pneumonia is a type of pneumonia that occurs outside of a hospital setting. Nosocomial or hospital acquired pneumonia is pneumonia that occurs 48 hours or more after admission to the hospital. In this case study, we look at how pneumonia affects the respiratory system and how it’s treated. The purpose of this study is to warn professionals to the possibility of a pneumonia diagnosis. This is the case report of 24-year-old male patient. He was diagnosed with pneumonia. His treatment was starting and after 7 treatments, he became completely recovered. For his disease diagnosis different tests are also performed.